대학 연구활동종사자의 식생활실태, 비타민 D 영양상태 및 혈액 임상지표 분석 - 황정현(Jung Hyun Hwang); 이홍미(Hong Mie Lee); 김정희(Jung Hee Kim) (Korean journal of community nutrition, 2019)
Objectives: Although the number of laboratory workers is constantly increasing every year, few studies have been conducted on the health and nutritional status of these research workers. This study determined the health status of laboratory workers by analyzing their anthropometric indices, dietary life, vitamin D status and blood clinical indices. Methods: The subjects consisted of 100 female laboratory workers. This study investigated their diet, anthropometric indices, vitamin D status and blood clinical indices. The subjects were divided into two groups according to their duration of working in a laboratory (<1 year, $${≥}_-1year$$). Results: The average age and body mass index (BMI) of subjects were 23.18 years and $21.51kg/m^2$, respectively Those subjects with over 1 year employment ($${≥}_-1year$$) had a significantly higher waist-hip ratio than that of the subjects with the less than 1 year employment (<1 year). The mean serum vitamin D level of all the subjects was 10.04 ng/mL, which is close to a level of vitamin D deficiency. There was a significantly higher average intake of calories in the over 1 year employment group as compared to that of the less than 1 year employment group. The frequency of eating sweet snacks was significantly higher for the over 1 year employment group. The correlation analysis showed a significant positive correlation between the serum 25-(OH)-vitamin D level and the time of exposure to sunlight, while dietary intake of vitamin D did not show correlation with the serum 25-(OH)-vitamin D level. However, the serum 25-(OH)-vitamin D level was also negatively correlated with both the percentage of body fat and visceral fat. Conclusions: Laboratory workers are a very high risk group in terms of their nutritional status of vitamin D. Therefore, they need greater time of exposure to sunlight as well as increasing their dietary consumption of vitamin D. In addition, it is important for laboratory worker to practice regular and balanced dietary habits in order to maintain a healthy life.